Prognostic value of the left ventricular ejection fraction reserve acquired by gated myocardial perfusion SPECT in patients with CAD and reduced stress LVEF - Zhang, Shuang; Meng, Jingjing; Zhou, Yihan; Lv, Lijun; Zhang, Xiaoli (Frontiers in Cardiovascular Medicine, 2024)
Purpose Left ventricular ejection fraction (LVEF) strongly predicts cardiac events. However, conflicting findings exist regarding the prognostic value of the LVEF reserve (ΔLVEF) when measured by gated single-photon emission computed tomography myocardial perfusion imaging (SPECT G-MPI). In particular, data related to the prognostic value of ΔLVEF when measured by SPECT in patients with reduced LVEF are scarce. In this study, we aimed to evaluate the prognostic value of ΔLVEF when acquired by SPECT G-MPI in patients with coronary artery disease (CAD) and a LVEFStress < 60%. Methods We retrospectively recruited 260 consecutive patients diagnosed with CAD by coronary angiography (CAG) and a LVEFStress < 60%, as determined by SPECT G-MPI. These patients were followed up for 33.4 ± 7.6 months. The patients were divided into two groups (ΔLVEF > 0% and ΔLVEF ≤ 0%), and survival analyses were conducted. The primary endpoints were major adverse cardiac events (MACEs), a composite of all-cause death, nonfatal myocardial infarction, unplanned coronary revascularization, and hospitalization for unstable angina. Results We observed 69 MACEs (26.5%). The cumulative incidence of MACEs in patients with ΔLVEF ≤ 0% was significantly higher than in patients with ΔLVEF > 0% (P = 0.042). Multivariate Cox regression further revealed that a ΔLVEF ≤ 0% represented an independent predictor of MACEs (adjusted hazard ratio [HR]: 1.276; 95% confidence interval [CI]: (1.006, 1.618), P = 0.045). Adding a ΔLVEF ≤ 0% to traditional myocardial perfusion and function variables evaluated by MPI significantly improved the ability to predict MACEs (P = 0.044). Conclusions Determining ΔLVEF by SPECT G-MPI was associated with MACEs and improved risk stratification compared to prediction models based on traditional perfusion and functional parameters in CAD patients with left ventricular dysfunction, particularly those with no or mild myocardial ischemia.